Pengaruh Kepemimpinan, Kompensasi dan Motivasi terhadap Komitmen Kerja SPG di Mall PGB Merdeka. - Norman, Efrita; Djamil, Masyhudzulhak; Santoso, Iman (Jurnal Manajemen, 2015)
This research is aimed to analysis whether there is the effect of leadership, compensation, and motivation toward work commitment the SPG of Merdeka PGB Mall simultaneously. The writer used survey method research which is kuantitatif approach. The sample of the research used by random purpose sampling technique which contains 84 respondents; and the amount of population is 500 persons. The result of this research shows that leadership, compensation and motivation are influenced toward work commitment the SPG of Mall Merdeka PGB Bogor simultaneously. The effect of contribution is 52,1% and the remaining 47,9% is influenced by other factors which are not be main focus of this research, such as SPG education background and organization culture.